2019
DOI: 10.1016/j.jdermsci.2019.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Fargesin inhibits melanin synthesis in murine malignant and immortalized melanocytes by regulating PKA/CREB and P38/MAPK signaling pathways

Abstract: Background: Fargesin is commonly used in the treatment of allergic rhinitis, inflammation, sinusitis and headache. Objective: The aim of the study is to investigate a new function of fargesin against melanin production and its underlying molecular mechanism. Methods: B16F10 mouse melanoma cells, Melan-a and human epidermal melanocytes were treated with different concentrations of fargesin for the indicated time. The extracellular and cellular melanin content was detected by spectrometry at 490 nm and 405 nm, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 28 publications
(28 reference statements)
1
21
0
Order By: Relevance
“…The mitoses, cell polarity, and differentiation are all managed by PKC ζ . A study indicated that the activation of PKC ζ could also increase the development of synapses and transfer the amount of melanosome into adjoining cells [ 41 ]. Our current experiment showed less significance of the PTE effect on the PKC ζ level ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…The mitoses, cell polarity, and differentiation are all managed by PKC ζ . A study indicated that the activation of PKC ζ could also increase the development of synapses and transfer the amount of melanosome into adjoining cells [ 41 ]. Our current experiment showed less significance of the PTE effect on the PKC ζ level ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…We attempted to identify the common pathways that are involved in both melanogenesis or carcinogenesis and SRA signaling. The literatures search revealed that p38 MAPK [ 14 , 21 ] and Notch-1 [ 20 , 22 ] are indeed involved in both pathophysiological processes. Hence, we measured the activation of p38 and the cleavage of Notch1 by western blotting after inhibiting SRA.…”
Section: Resultsmentioning
confidence: 99%
“…We attempted to identify the common pathways that are involved in both melanogenesis or carcinogenesis and SRA signaling. The literatures search revealed that p38 MAPK [14,21] and Notch-1 [20,22] are indeed involved in both https://doi.org/10.1371/journal.pone.0237577.g002…”
Section: Plos Onementioning
confidence: 99%
“…It is well known that the PKA signaling pathway is also involved in melanin synthesis [8,13,14,15]. PKA can be activated by the elevation of cellular cAMP, and its activation increases MITF transcriptional activity through CREB phosphorylation, resulting in the protein expression of tyrosinase, TRP-1, and TRP-2 [13,14,15]. Therefore, to determine whether the effects of LQ or LQG on melanin synthesis were also mediated by the PKA signaling pathway, we used a PKA inhibitor (H-89).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, protein kinase A (PKA) signaling is also known to play crucial roles in melanogenesis. PKA activation can lead to the phosphorylation of cyclic AMP (cAMP)-responsive element-binding protein (CREB) which, in turn, enhances MITF expression [8,13,14,15]. Another signaling pathway involved in melanogenesis regulation is the phosphatidylinositol-3-kinase (PI3K)/Akt signaling.…”
Section: Introductionmentioning
confidence: 99%